SpaceOps 2008 Conference 2008
DOI: 10.2514/6.2008-3434
|View full text |Cite
|
Sign up to set email alerts
|

GOES-13 Propulsion Modeling

Abstract: The Geostationary Operational Environmental Satellite (GOES) 13 is the first in a new series of weather satellites. Compared to previous GOES satellites, GOES-13 has improved Image Navigation and Registration (INR) accuracy, can continue imaging during eclipse periods, periodically yaw-flips to provide better instrument cooling, and uses daily momentum dumping maneuvers to offset solar torque generated by the single solar array. Post launch testing showed that GOES-13 met all INR requirements, but post-maneuve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…An important contributor to NS maneuver cross-coupling is impingement of the thruster plumes on the solar array of the satellite, which deflects some of the thruster exhaust, and thereby thrust, in an unintended direction (see, e.g., Gibbs et al 2008). The magnitude and direction of the deflected thrust depends on the orientation of the solar array with respect to the thrusters at the time of firing.…”
Section: Cross-coupling Prediction Errormentioning
confidence: 99%
“…An important contributor to NS maneuver cross-coupling is impingement of the thruster plumes on the solar array of the satellite, which deflects some of the thruster exhaust, and thereby thrust, in an unintended direction (see, e.g., Gibbs et al 2008). The magnitude and direction of the deflected thrust depends on the orientation of the solar array with respect to the thrusters at the time of firing.…”
Section: Cross-coupling Prediction Errormentioning
confidence: 99%
“…NEWOAD also solved for an EW ISEC parameter, but inclusion of ISEC did not have a significant effect on other parameter estimates. NEWOAD used values for the daily momentum-dumping v that were determined after applying post-PLT modifications to the propulsion model and thruster calibration 18 by the operational OATS during PLT are slightly biased compared to the calibrated values, but the effect on the range and landmark residuals is barely noticeable in the 24-hour predictive plots. This is verified by the similarity in the predictive range residuals of Fig.…”
Section: Iii1 Oad Analysis Toolsmentioning
confidence: 99%
“…Investigation revealed that North jet plume impingement on the solar array produced a force sufficient to cause this longitude drift error. A plume impingement model was developed and with minor adjustment to thruster force and cant angles 4 3 remained when the spacecraft was upright, but not when inverted. Additional maneuver modeling errors were eliminated as a potential source of the problem because changes in angular momentum across the maneuvers were well modeled using existing propulsion and plume impingement models.…”
Section: Introductionmentioning
confidence: 99%